The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/en15041437
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Digitalization in the Energy Sector—The Managerial Perspective from the Catching Up Economy

Abstract: This article attempts to identify the key forces driving the successful digitalization of the energy sector, ensuring improvements in the energy triangle including sustainability, stability, and economic performance. The article sheds light on the diverse energy priorities at supra-, national, and managerial levels, and the role of digitalization in achieving these objectives. Catching up economies (such as Poland), being post-socialist EU member states, in order to transform its energetic sector, must overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
0
24
0
1
Order By: Relevance
“…Positive implications of applying digital technologies to various use cases throughout the economy and the value generated can come as economic gain (e.g., from improved efficiencies) or societal benefit (e.g., more reliable, decarbonized electricity generation) [2,6]. A recent study based on an E-survey [7] found that expected improvements in economic performance is the main driver for the uptake of digital technologies in the Polish energy sector. The EU's assessment and roadmap for the digital transformation of the energy sector summarizes the potential of digital technology applications along the energy value chain [69].…”
Section: Digitalization In the Electricity Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive implications of applying digital technologies to various use cases throughout the economy and the value generated can come as economic gain (e.g., from improved efficiencies) or societal benefit (e.g., more reliable, decarbonized electricity generation) [2,6]. A recent study based on an E-survey [7] found that expected improvements in economic performance is the main driver for the uptake of digital technologies in the Polish energy sector. The EU's assessment and roadmap for the digital transformation of the energy sector summarizes the potential of digital technology applications along the energy value chain [69].…”
Section: Digitalization In the Electricity Systemmentioning
confidence: 99%
“…There is currently not a common set of definitions of digitization, digitalization and digital transformation in the electricity sector. Digitalization, for example, has been defined both from a data-centric perspective [36,37] ("digitalization as exploiting novel, large-scale data flows for optimizing some processes") and a rather process-centric perspective [2,7] ("digitalization as wide application and uptake of ICT converging physical and digital spheres").…”
Section: Defining Digitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Digitalization leads to the overall replacement and enhancement of energy use systems, creating a sustainable energy development platform that efficiently distributes energy resources (Fatai Adedoyin et al, 2021; Światowiec‐Szczepańska & Stępień, 2022). Consequently, a narrative implies that digitization enhances the working‐age population's efficiency, knowledge, and abilities, increasing productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One major challenge is the additional battery degradation incurred by the repeated charging and discharging cycles of bidirectional V2G implementation [281] . For the convenience and safety of their vehicles, drivers of electric vehicles usually charge in advance or ensure high charging levels for their electric vehicles [282] , which would preclude them from actively participating in two-way V2G services. Future researches should focus on intelligent scheduling and valuation technologies of V2G as well as digital battery management technologies.…”
Section: Transportation Systemsmentioning
confidence: 99%